Determinants of farmlevel technical efficiency among adopters of improved maize production technology in Western Ethiopia - Alene, A.; Hassan, R.M. (2003)
A translog stochastic production fronter was used to analyse the technical efficiency of small farmers using improved maize production technology in Western Ethiopia. The study estimated a mean technical efficiency for the entire sample of 76%, indicating that a significant potential for gains from efficiency improvement in maize production remains to be exploited even among users of improved technology. The study also revealed that farm size, education, access to credit and timely availability of modern inputs are important determinants of technical efficiency among maize producers in Ethiopia. Policies and strategies that promote rural education, credit, timely availability of inputs through better infrastructure and markets will be greatly instrumental in realising considerable gains in maize production with available farm resources through more efficient and appropriate use of improved technology.